A Cognitive-Ecological Explanation of Intergroup Biases. (July 2018) - Alves, Hans; Koch, Alex; Unkelbach, Christian
People often hold negative attitudes toward out-groups and minority groups. We argue that such intergroup biases may result from an interaction of basic cognitive processes and the structure of the information ecology. This cognitive-ecological model assumes that groups such as minorities and out-groups are often novel to a perceiver. At the level of cognition, novel groups are primarily associated with their unique attributes, that is, attributes that differentiate them from other groups. In the information ecology, however, unique attributes are likely to be negative. Thus, novel groups, and by proxy minorities and out-groups, tend to be associated with negative attributes, leading to an evaluative disadvantage. We demonstrated this disadvantage in three experiments in which participants successively formed impressions about two fictional groups associated with the same number of positive and negative attributes. Participants preferred the first group over the novel group as long as the groups' unique attributes were negative.